Search of the solution of a transport task by means of the software - Shulgina-Tarachshuk, A.S.; Toleuhanova, R.Gh. (Bulletin of the Karaganda University. Mathematics Series, 2016)
The article is devoted to research of applied methods of mathematical modeling for the solution of economic tasks by means of the tabular processor. The solution of a transport task, that is finding of the minimum expenses of basic suppliers is provided under the set conditions. The tabular processor helps to find the optimal solution of an economic task.